Jumlah Kepala Sekolah Dan Guru Menurut Kelompok Umur Provinsi DKI Jakarta, Lampung, Nusa Tenggara Timur, Dan Sumatera Selatan Tahun 2023/2024 - Surya Kusuma, Noval; Yudha Witama, Fiyado; Ramadhan, Rizki; Az Zikri Taufik, Wildan; Rosyani, Perani (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This study analyzes the age distribution of school principals and teachers in South Sumatra Province to understand the demographic characteristics of educators and their implications for educational policy planning. The findings show that the median age of educators is 40.77 years, while the average age is around 42.54 years. These results indicate that most educators in this province are approaching retirement age, suggesting potential challenges in educator regeneration. This research highlights the importance of recruiting new teachers and continuous training programs to ensure proper adaptation to developments in teaching methods and technology. It is recommended that educational policies focus on balancing experience and fresh energy through mentorship programs and competence development. These measures aim to maintain educational quality and prepare for sustainable regeneration to face future challenges.